2012
DOI: 10.3233/jad-2012-120805
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Alzheimer's Disease with the GSK-3 Inhibitor Tideglusib: A Pilot Study

Abstract: This pilot, double-blind, placebo-controlled, randomized, escalating dose trial explored the safety and efficacy of tideglusib, an inhibitor of glycogen synthase kinase-3, in Alzheimer's disease (AD) patients. Thirty mild-moderate AD patients on cholinesterase inhibitor treatment were administered escalating doses (400, 600, 800, 1,000 mg) of tideglusib or placebo (ratio 2 : 1) for 4, 4, 6, and 6 weeks, respectively. The primary objective was to evaluate the safety and tolerability of tideglusib with strict cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(162 citation statements)
references
References 31 publications
3
156
0
3
Order By: Relevance
“…A placebo-controlled, escalating-dose Phase IIa clinical trial in 30 patients with mild-to-moderate AD treated for 20 weeks showed positive trends on the MMSE and ADAS-Cog tests [50]. The compound, with orphan drug status designation by both US FDA and EMA, was also tested in a 1-year study (TAUROS) in 146 patients with PSP, but despite a signal toward reduced brain atrophy in a subgroup analysis [51], the study primary end points were not met [52].…”
Section: The Role Of Phosphorylation In Tau Pathologymentioning
confidence: 97%
“…A placebo-controlled, escalating-dose Phase IIa clinical trial in 30 patients with mild-to-moderate AD treated for 20 weeks showed positive trends on the MMSE and ADAS-Cog tests [50]. The compound, with orphan drug status designation by both US FDA and EMA, was also tested in a 1-year study (TAUROS) in 146 patients with PSP, but despite a signal toward reduced brain atrophy in a subgroup analysis [51], the study primary end points were not met [52].…”
Section: The Role Of Phosphorylation In Tau Pathologymentioning
confidence: 97%
“…It increases the levels of neurotrophic peptide insulin growth factor 1 (IGF-1), and promotes endogenous hippocampal neurogenesis in vitro and in vivo through GSK-3b inhibition [11]. Clinical trials with tideglusib show good tolerability (Phase I study, healthy volunteers, oral daily dosages between 50 and 1200 mg, up to 14 days) [12]. A Phase IIa study on 30 AD patients (400 to 1000 mg daily, p.o., 15 weeks) confirms the good tolerability of tideglusib and provides signs of efficacy in mild to moderate AD patients [11].…”
Section: Tau Kinase Inhibitorsmentioning
confidence: 98%
“…Um dos compostos da classe das TDZDs, conhecido como tideglusibe (Figura 2), foi planejado para o tratamento da doença de Alzheimer e da paralisia supranuclear progressiva, atuando como um inibidor reversível da GSK-3α α β (TOLOSA et al, 2014;HOGLINGER et al, 2014;DEL SER et al, 2013). A proposta da ligação de tiazolidinedionas como o tideglusibe à isoforma α , envolve a interação com o sítio de ligação do substrato por ligações de hidrogênio por meio dos aminoácidos arginina 96 e lisina 205 e interações de elétrons com a tirosina 216 da estrutura da enzima (SILVA et al, 2014).…”
Section: Figura 1 Efeitos De Gsk-3 Na Atividade Da Enzima Glicogêniounclassified